REFRACTIVE INDEX OF CaAl2Si2O8 GLASS AND CRYSTALLINE ANORTHITE AT PRESSURES UP TO 5.0 GPA - Kuryaeva R.G.; Kirkinskii V.A.; Surkov N.V. (My University, 2007)
The pressure behaviour of the refractive index of CaAl 2 Si 2 O8 glass (d=2.69 g/cm3 ) was studied in a range 0-5.0 GPa. This glass was chosen as the object of investigation because of 1) the glass composition corresponds to those of the mineral anorthite (the end-member feldspars), 2) as contrasted to others glasses of the end-members feldspars the structure of CaAl 2 Si 2 O8 glass is similar with the crystal structure.